Implementation of Technopreneurship in Culinary Departement of Vocational High School - Triati; Muhammad Giatman; Yuliana (Enrichment : Journal of Management, 2022)
This study aims to find out how to implementing technopreneurship in the culinary department at SMKN 2 Bukittinggi. This study uses a qualitative descriptive research approach. The research instrument was in the form of a questionnaire filled out by students and then analyzed to see the proportion of student interest and the form of entrepreneurship they had in the use of social media platforms. The results showed that 78% of the students were doing entrepreneurship activities using social media. Of the number of students who use the WhatsApp social media platform as much as 50% of the total number of students. They take advantage of information technology in the form of easy internet access with their social media account platforms in entrepreneurship.